OnlyFans and Deep Fake Porn – Can We Accept the Former but Condemn the Latter? - Räsänen, Joona (Informa UK Limited, 2026)
Many people think that producing online pornography, such as creating sexual content at OnlyFans, is permissible. Many of the same people also think that creating deepfake pornography without or against the consent of the person is wrong. I argue that accepting online sex work is inconsistent with judging pornographic deepfakes as worse than non-pornographic deepfakes. This claim resembles similarity with a broader problem in sexual ethics raised by David Benatar. I apply Benatar’s argument in the context of online sexual activities to highlight the ethical issues recent technological developments raise. I do this neither as a case against the permissibility of online sex work nor as a defense of pornographic deep fakes. The purpose is to point out the inconsistency. One could avoid the problem by extending or limiting the range of permissible sexual practices online. But if I am right, we cannot both accept OnlyFans and condemn non-consensual pornographic deep fakes.